Experimental Transmission of Bovine Digital Dermatitis to Sheep: Development of an Infection Model. Issue 2 (March 2018) - Wilson-Welder, Jennifer H.; Nally, Jarlath E.; Alt, David P.; Palmer, Mitchell V.; Coatney, John; Plummer, Paul
Digital dermatitis is an infectious cause of lameness primarily affecting cattle but also described in sheep, goats, and wild elk. Digital dermatitis is a polymicrobial infection, involving several Treponema species and other anaerobic bacteria. Although the exact etiology has not been demonstrated, a number of bacterial, host, and environmental factors are thought to contribute to disease development. To study host–bacterial interactions, a reproducible laboratory model of infection is required. The objective of this study was to demonstrate key aspects of bovine digital dermatitis lesions in an easy-to-handle sheep model. Crossbred sheep were obtained from a flock free of hoof disease. Skin between the heel bulb and dewclaw was abraded before wrapping to emulate a moist, anaerobic environment. After 3 days, abraded areas were inoculated with macerated lesion material from active bovine digital dermatitis and remained wrapped. By 2 weeks postinoculation, experimentally inoculated feet developed erosive, erythematous lesions. At 4 weeks postinoculation, microscopic changes in the dermis and epidermis were consistent with those described for bovine digital dermatitis, including erosion, ulceration, hyperkeratosis, ballooning degeneration of keratinocytes, and the presence of neutrophilic infiltrates. Silver staining of lesion biopsy sections confirmed that spirochetes had penetrated the host epidermis. The model was then perpetuated by passaging lesion material from experimentally infected sheep into naïve sheep. This model of bovine digital dermatitis will allow for future novel insights into pathogenic mechanisms of infection, as well as the development of improved diagnostic methods and therapeutics for all affected ruminants.